Fibroid Uterus Updates In Treatment - Aaisha Aman; Shahina Ishtiaq; Rubina Hussain (ziauddin University, 2024)
Fibroids or leiomyoma of myometrium are the most common benign tumor in females. There are currently many modalities, both medical and surgical, for the management of fibroid in today's practice such that it is often confusing as to which treatment to apply to which patient. Fibroid patients often present with a variety of symptoms and demographic aspect. Therefore a single guideline is not sufficient to encompass the case management for a specific Fibroid patient. Similarly the incidence of uterine sarcoma in patients undergoing fibroid treatment is thought to be minimal, but there is a current debate whether this risk is underestimated. The novel approach towards fibroids has allowed greater extent of uterine preservation but at the cost of decreased direct histological access, hence resulting in delay of diagnosis, especially in the case where uterine sarcoma is a possibility. Therefore gynecologists have to face the clinical dilemma to diagnose accurately and choose the most suitable treatment from the vast array of options available for each patient. The purpose of this article is to reconsider the different methods of treatments available and apply the most tailored treatment in each patient. This is a platform to better counsel for fibroid patients and their management. Key Words: Fibroid uterus, case management, Ulipristal, Aromatase inhibitors, Invasive procedures.